Effect of the Ethyl Acetate Fraction of Eugenia uniflora on Proteins Global Expression during Morphogenesis in Candida albicans - Silva-Rocha, Walicyranison P.; Azevedo, Matheus F. de; Ferreira, Magda R. A.; Silva, Julhiany de Fatima da [UNESP]; Svidzinski, Terezinha I. E.; Milan, Eveline P.; Soares, Luiz A. L.; Rocha, Keyla B. F.; Uchoa, Adriana F.; Mendes-Giannini, Maria J. S. [UNESP]; Fusco Almeida, Ana M. [UNESP]; Chaves, Guilherme M. (Frontiers Media Sa, 2017)
Candida albicans is able to switch from yeast to hyphal growth and this is an essential step for tissue invasion and establishment of infection. Due to the limited drug arsenal used to treat fungal infections and the constant emergence of resistant strains, it is important to search for new therapeutic candidates. Therefore, this study aimed to investigate by proteomic analysis the role of a natural product (Eugenia uniflora) in impairing hypha formation in C. albicans. We also tested the potential action of E. uniflora to prevent and treat oral candidiasis induced in a murine model of oral infection and the ability of polymorphonuclear neutrophils to phagocytize C. albicans cells treated with the ethyl acetate fraction of the extract. We found that this fraction greatly reduced hypha formation after morphogenesis induction in the presence of serum. Besides, several proteins were differentially expressed in cells treated with the fraction. Surprisingly, the ethyl acetate fraction significantly reduced phagocytosis in C. albicans (Mean 120.36 +/- 36.71 yeasts/100 PMNs vs. 44.68 +/- 19.84 yeasts/100 PMNs). Oral candidiasis was attenuated when C. albicans cells were either pre-incubated in the presence of E. uniflora or when the fraction was applied to the surface of the oral cavity after infection. These results were consistent with the reduction in CFU counts (2.36 vs. 1.85 Log10 CFU/ml) and attenuation of tissue damage observed with histopathological analysis of animals belonging to treated group. We also observed shorter true hyphae by direct examination and histopathological analysis, when cells were treated with the referred natural product. The E. uniflora ethyl acetate fraction was non-toxic to human cells. E. uniflora may act on essential proteins mainly related to cellular structure, reducing the capacity of filamentation and attenuating infection in amurinemodel, without causing any toxic effect on human cells, suggesting that itmay be a future therapeutic alternative for the treatment of Candida infections.
Keywords: Candida albicans; phagocytosis; morphogenesis; proteomics; Eugenia uniflora; murine model